Establishment of Reference Interval and Aging Model of Homocysteine Using Real-World Data - Ma, Chaochao; Li, Lei; Wang, Xinlu; Hou, Li’an; Xia, Liangyu; Yin, Yicong; Cheng, Xinqi; Qiu, Ling (Frontiers in Cardiovascular Medicine, 2022)
Objective: The level of Homocysteine (Hcy) in males is generally higher than that of females, but the same reference interval（RI）is often used in clinical practice. This study aims to establish a sex-specific RI of Hcy using five data mining algorithms and compare these results. Furthermore, age-related continuous RI was established in order to show the relationship between Hcy concentration distribution and age. Method: 20801 individuals were included in the study and Tukey method was used to identify outliers in subgroups by sex and age. Multiple linear regression and standard deviation ratio (SDR) was used to determine whether the RI for Hcy needs to be divided by sex and age. Five algorithms including Hoffmann, Bhattacharya, expectation maximization (EM), Kosmic and refineR were utilized to establish the RI of Hcy. Generalized Additive Models for Location Scale and Shape (GAMLSS) algorithm was used to determine the ageing model of Hcy and calculate the age-related continuous RI. Results: RI of Hcy needed to be partitioned by sex (SDR=0.735>0.375). RIs established by Hoffmann, Bhattacharya, EM (for females) and Kosmic are all within the 95% CI of reference limits established by refine R. The Sex-specific ageing model of Hcy showed that the upper limits of the RI of Hcy declined with age beginning at age of 18 and began to rise approximately after age of 40 for females and increased with age for males. Conclusion: The RI of Hcy needs to be partitioned by sex. The RIs established by the five data mining algorithms showed good consistency. The dynamic sex and age-specific model of Hcy showed the pattern of Hcy concentration with age and provide more personalized tools for clinical decisions.